Implementation of compensation-sensitive shot-style-feedback of aiming point training data at the Swiss Shooting Federation - Tartaruga, D.; Kredel, R. (Current Issues in Sport Science, 2025)
Introduction The practical application of scientific knowledge is essential for improving performance in Olympic air rifle shooting. At the Swiss Shooting Federation, for example, we have implemented an innovative training concept based on our research into compensation-sensitive shot styles and the importance of individual movement phases (Tartaruga & Kredel, 2021, 2022, 2024).